ARch4models: a tool to augment physical scale models - Eloy, S.; Costa, F.; Dias, J.; Mariana Lopes (eCAADe 2017 Conference, 2017)
This paper focus on the development and evaluation of a computer tool that enriches physical scale models of buildings, which are commonly used during architecture and civil engineering design processes. The main goal of this work is to enable designers, namely architects, to use the affordances of the physical scale models, by enhancing them with digital characteristics that can be easily changed, allowing an enriched interaction of the designer with such models. Our in-house developed Augmented Reality tool, referred to as ARch4models, augments the user experience with visual features and interactive capabilities, not possible to accomplish with physical models (see this video in https://goo.gl/5zbdTQ). The tool allows the coherent registration between the real and the digital in the same space. Satisfaction evaluation studies were conducted that have shown that ARch4models improves the building design process when compared with a traditional methodology employing solely physical scale models.